Modeling of Miniaturized, Multiband and Ultra-Wideband Fractal Antenna - Zakariyya, Sikiru Olayinka (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2015)
Due to advancements in communication technology, there is an increase in the demand of small size, low cost, multiband and wideband antennas. With a view to address these demands, a fractal design was employed in this study. Despite the advantages provided by these antennas, miniaturization and performance enhanced further by using a partial ground plane. This research work presents an antenna which is based on the well-known Sierpinski Carpet fractal with iteration factor of 1/3. The antenna was designed up to third iteration with a view of achieving miniaturization. A simple antenna was designed for purpose of comparison, by using a simple rectangular slot at the middle of the patch and a 34.88% size reduction was achieved at the same resonant frequency. This is achieved by introducing defected ground structure into the design which gives the antenna wideband behaviour with bandwidth of 442MHz at centre frequency of 2.45GHz. A multiband square patch antenna using third order Sierpinski Carpet was designed to operate at 1.88GHz alongside a new circular fractal antenna up to third iteration with a partial ground structure to achieve ultra wideband behaviour with a bandwidth of 8.18GHz at centre frequency of 2.54GHz. The designed antenna was simulated using three dimensional finite integration time domain commercial software microwave studio. The objective of this thesis to design a fractal antenna with small size, multiband and wideband behaviour was largely met. Keywords: Miniaturized, Multiband and Ultra Wideband antenna, Fractal geometries, Partial Ground Structure.

İletişim teknolojisindeki gelişmeler ile, küçük boyutlu, düşük maliyetli, çok bantlı ve geniş bantlı anten taleplerinde büyük bir artış olmuştur. Bu talepleri karşılamak üzere yapılan bu çalışmada fraktal anten tasarımları gerçekleştirilmiştir. Fraktal antenlerin sağladığı bu avantajlara rağmen, performansının artırılması ve boyutlarının küçültülmesi için kısmi yer düzlemi uygulamak gerekmiştir. Bu çalışma, 1/3 yineleme faktörü ile bilinen Sierpinski Halı fractal anten tasarımına dayalı bir tasarım içermektedir. Anten, minyatür anten elde etmek amacıyla üçüncü yineleme faktörüne (iterasyon) kadar tasarlanmıştır. Karmaşık yapıları ile bilinen fraktal antenlerin performansı ile karşılaştırma maksatlı basit bir anten tasarlanmış ve aynı rezonans frekansında antenin boyutunda %34.88 küçülme sağlanmıştır. Tasarımda, arızalı zemin yapısı kullanılarak, geniş band davranışı gösteren 442MHz’lik bir bant elde edilmiştir. Bu çalışmada, 1.88GHz frekansında üçüncü dereceden kare Sierpinski Halı ile kısmi yer düzlemli, dairesel fraktal anten tasarımı gerçekleştirimiştir. İki durum için de anten çok band ve çok geniş band elde etmek için üçüncü iterasyona kadar tasarlamnıştır. Kısmi yer düzlemi ile ultra geniş bant davranış gösteren dairesel fraktal anten, 2.54GHz merkez frekansında 8.18GHz’lik bir bant genişliğine sahiptir. Çalışma tam-dalga benzetim programı kullanılarak yapılmıştır. Bu tezin amacı olan, küçük boyutu, çok bantlı ve geniş bantlı davranış gösteren bir fraktal anten tasarımı büyük ölçüde gerçekleştirilmiştir. Anahtar Kelimeler: minyatür, Çok Bantlı ve Ultra Geniş Bantlı anten, Fraktal geometri, Kısmi yer düzlemi.
Master of Science in Electrical and Electronic Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Electrical and Electronic Engineering, 2015. Supervisor: Assist. Prof. Dr. Rasime Uyguroğlu.
Keywords: Electrical and Electronic Engineering; Antennas (Electronics); Broadband communication systems; Miniaturized, Multiband and Ultra Wideband antenna, Fractal geometries, Partial Ground Structure